(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2017)
Company growth depends on competitiveness and innovation, which are largely contingent on the scale and scope of research and development undertaken. In the new EU financial framework for 2014-2020, R&D funding is contingent on compliance with research planned with regional smart specialisations. The article reviews the literature on factors in competitiveness, as well as the importance of smart specialisation in shaping the development of the food sector in Poland. The main objective of the article is to present the role and importance of smart specialisation for companies in the food industry seeking to build a competitive position.